THE EFFECTIVENESS OF PICTURE AND PICTURE MODEL IN IMPROVING THE STUDENTS’ WRITING SKILLS AT 8TH GRADE STUDENTS OF SMPN 2 PANGKAJENE - Naing, Ince Rezky; Hamid, Radiah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research aimed to verify The Effectiveness of Picture and Picture Model in improving the students’ writing skills that focused on Content and Organization. The writer applied Pre-Experimental Method with One Group Pretest Post-test Design, and collected the data by giving Pre-test, treatment and Post-test. The sample of the research was Class VIII A of SMPN 2 Pangkajene which consisted of 23 students. The sample was taken by using Purposive Sampling Technique. The research findings showed that the 8th students of SMPN 2 Pangkajene had poor score in Pre-test. After treatment, their writing skills was significantly increase. The result of the research were the mean score of content obtained by the students through Pre-test was 55 and Post-test was 75 with the t-test value Content is greater than t-table (8.196> 2, 07387). Mean score of Organization Pre-test 51 and Post-test 74 with the t-test value organization is greater than t-table (10,106> 2, 07387). The Hypothesis Testing also was done by using SPSS 23 and showed that Sig (2-tailed) lower than level of significance (, 000 < 0.05). It means that there is significance difference between before and after giving the treatment. It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded that the use of Picture and Picture Model in writing activity could improve the students writing skills in Recount Text exactly in making good Content and Organization.